การจัดสมดุลสายการผลิตแบบหลายผลิตภัณฑ์ภายใต้เงื่อนไขเวลาไม่คงที่ในการผลิตเสื้อผ้าสำเร็จรูป - นรินทร์ จึงจำเริญกิจ (จุฬาลงกรณ์มหาวิทยาลัย, 2010)
The labor is a main factor in garment apparel. Hence, the production planning and the line balancing are required to increase the production efficiency. This research presents the study of the line balancing in the garment apparel process under the variable work element times by using the computer program. The methods adopted to compare the efficiency of line balancing in the apparel factory are the heuristic multiple-product line balancing with workload leveling method, the COMSOAL single-product line balancing method, and the COMSOAL multiple-product line balancing method. It is found that the heuristic multiple-product line balancing with workload leveling method can increase the production rate about 63.64% and reduce the calculating time for line balancing about 91.21% as compared to the previous technique.